The Role of Emotional Information in Banner Blindness - Sapronov, Frol; Gorbunova, Elena (Frontiers in Psychology, 2022)
Modern theories in affective science postulate that emotional stimuli can affect subject’s attention. Emotional stimuli can guide and capture visual attention, which may be related to evolutional importance of quick reactions for emotional objects in the real life. The study examined the influence of valence and arousal of advertisement on the banner blindness phenomenon – ignoring the advertisement or interface details similar to it on the website. In two experiments participants were asked to find the information on the website, where different banners were placed. In the first experiment banners had the same valence, but different arousal. In the second experiment, the banners had different valence, but equal arousal. Contrary to the classical studies in affective science, we found that banners with neutral valence were recognized better as compared to negative and positive ones. The results are discussed in terms of user experience contributing to banner blindness occurrence.